Identification of a cis-regulatory element involved in accumulation of human T-cell leukemia virus type II genomic mRNA. - Ohta, M (1988)
The X gene products of the human T-cell leukemia viruses type I and II are thought to be involved not only in viral replication but also in mediating the expression of certain cellular genes. These X gene products are known to be translated from doubly spliced viral mRNA, while viral structural proteins, such as the gag, pol, and env gene products, are translated from unspliced or singly spliced viral mRNA. One of the X gene products of human T-cell leukemia virus type II, tax2 protein, has been shown to be responsible for transcriptional stimulation from the viral long terminal repeat. The other X gene product(s) of human T-cell leukemia virus type II, the rex2 protein(s), is located in the nuclear fraction of virus-infected cells, but its function is not known. This article reports evidence that rex2 protein(s) enhances the accumulation of unspliced viral RNA by interacting posttranscriptionally, either directly or indirectly, with a cis-regulatory element downstream from the first splice donor site in the long terminal repeat.